1999
DOI: 10.1007/s002340050847
|View full text |Cite
|
Sign up to set email alerts
|

Changes in visibility of intracranial arteries on MRA with normal ageing

Abstract: We investigated age-related changes in the visibility of intracranial arteries on magnetic resonance angiography (MRA) and the influence of risk factors for stroke. We studied 230 adult patients without specific neurological deficits. MRA was performed using the three-dimensional time-of-flight technique with a spoiled gradient-recalled acquisition sequence. We classified internal carotid artery (IC) and the horizontal (M1) and distal (beyond M2) middle cerebral segments into 4 grades. Linear regression reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 13 publications
1
11
0
Order By: Relevance
“…16,17 A mild increase in vessel diameter with age could also explain, at least in part, the lower velocities observed in adults when compared with children with SCD. 18 We found an overall prevalence of 16% of intracranial stenoses detectable by MRA. In neurologically asymptomatic children with SCD, the frequency of stenoses detected by MRA is similar to our findings.…”
Section: Discussionmentioning
confidence: 63%
“…16,17 A mild increase in vessel diameter with age could also explain, at least in part, the lower velocities observed in adults when compared with children with SCD. 18 We found an overall prevalence of 16% of intracranial stenoses detectable by MRA. In neurologically asymptomatic children with SCD, the frequency of stenoses detected by MRA is similar to our findings.…”
Section: Discussionmentioning
confidence: 63%
“…The decline in cerebral blood fl ow with advancing age may be associated with certain changes in cerebrovascular hemodynamics such as decreased metabolic demands, higher hematocrit and lower partial pressure of carbon dioxide levels (Melamed et al 1980), vessel-size changes (Kusunoki et al 1999), and lower cardiac output (Safar 1990). Several investigations demonstrated the importance of age on the TCD velocities (Arnolds and von Reutern 1986;Brouwers et al 1990).…”
Section: Discussionmentioning
confidence: 99%
“…The decline in CBFV with age may be associated with certain changes in cerebrovascular hemodynamics such as (1) decreased CBF or metabolic demands, 25,26 (2) vessel-size changes, 27 and (3) lower cardiac output. 28,29 Aging is associated with a 20% to 30% decrease in CBF in healthy individuals between the ages of 20 and 80 years.…”
Section: Effect Of Age On Cbfv and Pimentioning
confidence: 99%
“…30 Aging is also associated with dilatation of major extracranial arteries and reduction of flow within parenchymal vessels. 27 Kusunoki et al 27 demonstrated poor visibility of the intracerebral ICA and M1 segment of the MCA on magnetic resonance angiography secondary to progressive kinking, elongation, and stenosis with advancing age.…”
Section: Effect Of Age On Cbfv and Pimentioning
confidence: 99%